Ancient West Mexico in the Mesoamerican ecumene - Williams, Eduardo (Archaeopress Pre-Columbian archaeology., 2020)
This volume presents a long-overdue synthesis and update on West Mexican archaeology. Ancient West Mexico has often been portrayed as a 'marginal' or 'underdeveloped' area of Mesoamerica. This book shows that the opposite is true and that it played a critical role in the cultural and historical development of the Mesoamerican ecumene.